Short term outcome of total knee replacement in Kashmiri population without co-morbidities - Wani, M. Ahsan; Ganaiee, Mushtaq Ahmed; Mir, Bashir Ahmed; Sultan, Asif; Islam, Muneebul (International Surgery Journal, 2019)
Background: The aim of the study was to evaluate the patients of osteoarthritis of knee prior to surgery and then 6 weeks after the total knee replacement surgery with regards pain, range of motion, stability, deformity, quadriceps power and support. Methods: This is a prospective follow up study. A minimum of 20 patients have been included in this study conducted in Department of Orthopedics, Bone and Joint Hospital Barzullah Srinagar, during the period of September 2014 to November 2016. Results: The average age of patients was 59.63 years, more than 35% of the patients belonged to the age group 66-70 years, majority of the patients were females (70%) in the whole study group. Most (88.89%) cases were bilateral, affecting both knees. The mean pre-operative range of motion in 94.38 degrees. The mean postoperative range of motion was 113.75 degrees. Patients were followed up at 2, 4, 6 weeks postoperatively. The average blood loss was 500 ml and the average operating time was one hour and 15 minutes and one hour. There was one deep vein thrombosis, one delayed wound healing, one common peroneal nerve palsy and one valgus deformity. Conclusions: The patients with more severely deformed knees, are more elderly, have more pain perception, their functional quality of life was impaired more, they were physically more dependent and their quality of life improves significantly after surgery.